1996
DOI: 10.1111/j.1432-2277.1996.tb00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver graft-transmitted glioblastoma multiforme. A case report and experience with 13 multiorgan donors suffering from primary cerebral neoplasia

Abstract: The transmission of donor-related malignancies by organ transplantation is a rather rare event. There has only been one report on the development of a brain tumor metastasis in liver transplantation. From September 1988 to January 1993, 342 donor hepatectomies with subsequent transplantation were performed at our center. The main donor diagnoses included subarachnoidal bleeding (n = 128; 37.4%), isolated head injury (n = 114; 33.3%), multiple injuries (n = 55; 16.1%), primary cerebral neoplasia (n = 13; 3.8%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…There is a high likelihood that significant stromal differences exist between the CNS and distant organs, such that extracranial glioblastoma metastases are difficult to develop. Lastly, there are reports of extracranial glioblastomas developed in recipients of kidney or liver transplanted from donors with glioblastomas [16][17][18][19]. The immunosuppressants used to prevent rejection of donor organs may further potentiate the development of these tumors in the recipient.…”
Section: Discussionmentioning
confidence: 98%
“…There is a high likelihood that significant stromal differences exist between the CNS and distant organs, such that extracranial glioblastoma metastases are difficult to develop. Lastly, there are reports of extracranial glioblastomas developed in recipients of kidney or liver transplanted from donors with glioblastomas [16][17][18][19]. The immunosuppressants used to prevent rejection of donor organs may further potentiate the development of these tumors in the recipient.…”
Section: Discussionmentioning
confidence: 98%
“…Two single-center retrospective case series, involving a total of 132 recipients of organs from 47 donors with CNS tumors, documented a transmission rate of 2.2-3% (91,92). Three large transplant registries have also provided data, albeit conflicting.…”
Section: Recommendationmentioning
confidence: 97%
“…Besides this there were seven reported cases of transmission of primary CNS tumors by 1997 (Lefrancois et al 1987;Morse et al 1990;ValBernal et al 1993;Ruiz et al 1993;Konigsrainer et al 1993;Colquhoun et al 1994;Jonas et al 1996;Bosmans et al 1997). These resulted in procurement of 18 transplantable organs (two kidneys, three hearts, two lungs and one kidney/pancreas).…”
Section: Primary Brain Tumorsmentioning
confidence: 88%
“…They noted that besides the case of transmission of a glioblastoma from one donor to two kidney transplant recipients, there were no other cases of tumor transmission in 34 donors with primary CNS tumors providing 84 organs, thus estimating the risk of tumor transmission of 3% (1/34) and the rate of transmitted tumor of 2% (2/84, Table 3). In 46 recipients of organs from 13 donors with primary brain tumor, Jonas et al (1996) found only a single case of transmission of glioblastoma to a liver transplant recipient. Interestingly there was no tumor transmission in the heart from the same donor.…”
Section: Primary Brain Tumorsmentioning
confidence: 96%